Single-Cell Transcriptome Analysis Decipher New Potential Regulation Mechanism of ACE2 and NPs Signaling Among Heart Failure Patients Infected With SARS-CoV-2 - Ma, Mengqiu; Xu, Yanhua; Su, Yang; Ong, Sang-Bing; Hu, Xingdong; Chai, Min; Zhao, Maojun; Li, Hong; Fan, Xiaojuan; Chen, Yingjie; Xu, Dachun; Xu, Xiaojiang (Frontiers in Cardiovascular Medicine, 2021)
Aims: COVID-19 patients with comorbidities such as hypertension or heart failure (HF) are associated with poor clinical outcomes. The cellular distribution of Angiotensin-converting enzyme 2 (ACE2), the critical enzyme for SARS-CoV-2 infection, in the human heart is unknown. We explore the underlying mechanism that leads to increased susceptibility to SARS-CoV-2 in patients with cardiovascular diseases and patients of cardiac dysfunction have increased risk of multi-organ injury compared with patients of normal cardiac function. Methods and Results: We analyzed single-cell RNA sequencing (scRNA-seq) data in both normal and failing hearts. The results demonstrated that ACE2 is present in cardiomyocytes (CMs) and non-CMs, while the number of ACE2-postive (ACE2+) CMs and ACE2 gene expression in these CMs are significantly increased in the failing hearts. Interestingly, both brain natriuretic peptides (BNP) and atrial natriuretic peptide (ANP) are significantly up-regulated in the ACE2+ CMs, which is consistent with other studies that ACE2, ANP and BNP increased in HF patients. We found that genes related to virus entry, virus replication and suppression of interferon-gamma signaling are all up-regulated in failing CMs, and the increase was significantly higher in ACE2+ CMs, suggesting that these CMs may be more vulnerable to virus infection. As the level of expression of both ACE2 and BNP in CMs were up-regulated, we further performed retrospective analysis of the plasma BNP levels and clinical outcomes of 91 COVID-19 patients from a single-center. Patients with higher plasma BNP were associated with significantly higher mortality and expression levels of inflammatory and infective markers. Conclusion: In the failing heart, the upregulation of ACE2 and virus infection associated genes could potentially facilitate SARS-CoV-2 virus entry and replication in these vulnerable cardiomyocyte subsets. COVID-19 patients with higher plasma BNP levels had poorer clinical outcomes. These observations may allude to a potential regulatory association between ACE2 and BNP in mediating myocarditis associated with COVID-19.